Devastating Mooren Ulcer Halt by Timely Aggressive Treatment - A Case Report: Poster Presentation - Case Report - Resident - Florentina Priscilia; Lily Raudah Putri; Annisa Windyani; Ferdy Iskandar; Triana Hardianti Gunardi; Yulia Aziza (Majalah Oftalmologi Indonesia, 2023)
Introduction : Mooren ulcer is a progressive and painful peripheral ulcerative keratitis of unknown cause. Study aims to show effective aggressive treatment for Mooren ulcer. Case Illustration : A 43-year-old man was admitted with a marked clinical worsening of the white tissue covering the cornea, accompanied by pain, redness, and blurry vision of the left eye. Initial examination showed visual acuity of 6/21cc. Peripheral corneal ulcer was found from 6 to 2 clock hours with superficial vascularization and epithelial defect. Patient underwent ancillary examinations with unremarkable findings. Patient was diagnosed with Mooren Ulcer and treated with artificial tears and steroid topical. Patient had no significant improvement; therefore conjunctival resection with immunosuppressive therapy were performed. At follow up, no pain was reported, vision improved to 6/15cc, and the ocular surface inflammation resolved. Discussion : Mooren ulcer is usually misdiagnosed since the clinical signs are similar to other differential diagnoses. The examination must be performed carefully to rule out autoimmune and corneal infection. Treatment goals are to halt the destructive process and promote reepithelization. The stepwise aggressive approach of Mooren Ulcer treatments is crucial. It starts directly with topical steroid to control the progression of inflammation. However, when used alone, topical steroid usually cannot prevent the rapid progression so conjunctival resection is needed to remove the source of collagenase production by cutting the perilimbal blood vessels’ access to the area of the ulcer. Combination with an immunosuppressant will effectively maintain a stable condition. Conclusion : Early diagnosis and aggressive treatment for Mooren ulcer are needed to prevent the rapid progression.